The Journey to Inflation Targeting : Easier Said than Done The Case for Transitional Arrangements along the Road - Laurens, Bernard (IMF Working Papers; Working Paper, 2015)
Countries with evolving monetary regimes that decide to embark on 'the Journey to inflation targeting' may not be able to adopt a full-fledged inflation targeting regime immediately. Those countries would be better off adopting transitional arrangements that take advantage of the informational content of monetary aggregates, developing an economic analysis capacity, and concentrating on monetay operations aimed at steering money market interest rates. This approach would allow the central bank to buy time for developing the building blocks for effective monetary policy, support transparent central bank communication, and limit the potential for undesirable outcomes along the road.